The Influence of Tutoring Business Management Innovations and Educational Technology Developments on Operational Efficiency in Binasi - Salzabilla, Siti Danisha; Rahmawati, Devi Kania; Arasyid, Siti Aisyah Nursyifa; Jannah, Rosyidatul; Sukmaya, Wulan (Jurnal Wacana Ekonomi, 2025)
Operational efficiency is the ability of an organization to provide products or services cost-effectively and on time by maintaining quality and customer satisfaction while reducing inputs, such as time, costs and resources. This is because technological developments continue to advance, creating various innovations in maintaining service quality. This research aims to determine the influence of innovation in tutoring business management and developments in educational technology on operational efficiency at BINASI. The approach used is a quantitative approach with a sample size of 50 respondents. The analysis method uses analysis by testing using the SPSS tool. The results of hypothesis testing show that there is an influence of innovation in tutoring business management and the development of educational technology on operational efficiency at BINASI.